Perineal Groove: Report of Two Cases and Review of the Literature - Cheng, Huiyan; Wang, Zhichao; Zhao, Qiang; Zhu, He; Xu, Tianmin (Frontiers in Pediatrics, 2018)
Perineal groove is a rare anoperineal congenital malformation and usually effect on newborn females. It is unknown to many clinicians and is usually leading to misdiagnosis. The pathogenesis of perineal is not clear. There are a few cases reported in current medical literature. The perineal groove of two new born babies were described in this report and the literature of cases on perineal groove were also reviewed and analyzed to improve the recognition of this disease.